EsxB, a secreted protein from Bacillus anthracis forms two distinct helical bundles. (3rd July 2015) - Fan, Yao; Tan, Kemin; Chhor, Gekleng; Butler, Emily K.; Jedrzejczak, Robert P.; Missiakas, Dominique; Joachimiak, Andrzej
Abstract The EsxB protein from Bacillus anthracis belongs to the WXG100 family, a group of proteins secreted by a specialized secretion system. We have determined the crystal structures of recombinant EsxB and discovered that the small protein (∼10 kDa), comprised of a helix‐loop‐helix (HLH) hairpin, is capable of associating into two different helical bundles. The two basic quaternary assemblies of EsxB are an antiparallel (AP) dimer and a rarely observed bisecting U (BU) dimer. This structural duality of EsxB is believed to originate from the heptad repeat sequence diversity of the first helix of its HLH hairpin, which allows for two alternative helix packing. The flexibility of EsxB and the ability to form alternative helical bundles underscore the possibility that this protein can serve as an adaptor in secretion and can form hetero‐oligomeric helix bundle(s) with other secreted members of the WXG100 family, such as EsxW. The highly conserved WXG motif is located within the loop of the HLH hairpin and is mostly buried within the helix bundle suggesting that its role is mainly structural. The exact functions of the motif, including a proposed role as a secretion signal, remain unknown.